Role of three different plants on simultaneous salt and nutrient reduction from saline synthetic wastewater in lab-scale constructed wetlands - Jesus J.M. (2017)
Constructed Wetlands (CWs) can be a valuable technology to treat high salinity wastewaters but it is not known their potential for removal of both nutrients and salt, and the type of plants to use. This study evaluated the effect of three plants on salt reduction and simultaneous nutrient removal in CWs microcosms with expanded clay and in hydroponic conditions. Initial values of the synthetic wastewater tested were EC = 15 dS m− 1, SAR = 151; NH4 +-N = 24 mg L− 1; PO4 3 −-P = 30 mg L− 1 and NO3 −-N = 34 mg L− 1. With expanded clay CW removal efficiency for NH4 +-N was 21, 88 and 85%, while for NO3 –-N, it was 4, 56 and 68% for Spartina maritima, Juncus maritimus and Arundo donax, respectively. PO4 3–-P was adsorbed completely in the expanded clay. However, in hydroponic system, removal efficiencies for NH4 +-N were 53 and 50%, while PO4 3–-P removal was 89 and − 14% for Spartina maritima and Juncus maritimus, respectively. Nutrient removal in planted microcosms was statistically higher than unplanted controls for NH4 +-N and PO4 3 −-P. However, salt removal was apparent in the hydroponic system only after 23 days of HRT, despite clear salt excretion visible in both Spartina maritima and Juncus maritimus. This study demonstrates the potential of two halophytic plants for saline wastewater treatment. However, salt removal in such a scenario could not be well documented and might prove to be impractical in future work. © 2016 Elsevier